The protection of the environment as an important task of local government in Poland - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
Currently, not to be underestimated is the role of local governments in the field of environmental protection. It is on their different levels that local authorities determine the efficiency of setting environmental standards for local communities. The efficient implementation of regional operational programs determines the possibility of implementing the principles of sustainable development.